2021
DOI: 10.3390/jcm10235555
|View full text |Cite
|
Sign up to set email alerts
|

Central Sleep Apnea Is Associated with an Abnormal P-Wave Terminal Force in Lead V1 in Patients with Acute Myocardial Infarction Independent from Ventricular Function

Abstract: Sleep-disordered breathing (SDB) is highly prevalent in patients with cardiovascular disease. We have recently shown that an elevation of the electrocardiographic (ECG) parameter P wave terminal force in lead V1 (PTFV1) is linked to atrial proarrhythmic activity by stimulation of reactive oxygen species (ROS)-dependent pathways. Since SDB leads to increased ROS generation, we aimed to investigate the relationship between SDB-related hypoxia and PTFV1 in patients with first-time acute myocardial infarction (AMI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…As they result in impaired cardiac and particularly atrial function, it is crucial to identify patients at risk with polysomnography. Our group has recently shown that the magnitude of the ECG parameter P-wave terminal force in lead V1 is associated with the apnea-hypopnea index and may thus serve as a readily available parameter to identify patients that should be screened for SDB by polysomnography ( 37 ). Treatment options for obstructive sleep apnea include automatic positive airway pressure, which has recently been shown to improve cardiopulmonary exercise capacity and left ventricular ejection fraction in patients with heart failure with reduced ejection fraction ( 38 ).…”
Section: Clinical Outlookmentioning
confidence: 99%
“…As they result in impaired cardiac and particularly atrial function, it is crucial to identify patients at risk with polysomnography. Our group has recently shown that the magnitude of the ECG parameter P-wave terminal force in lead V1 is associated with the apnea-hypopnea index and may thus serve as a readily available parameter to identify patients that should be screened for SDB by polysomnography ( 37 ). Treatment options for obstructive sleep apnea include automatic positive airway pressure, which has recently been shown to improve cardiopulmonary exercise capacity and left ventricular ejection fraction in patients with heart failure with reduced ejection fraction ( 38 ).…”
Section: Clinical Outlookmentioning
confidence: 99%